METODE DISKUSI TERBIMBING MENINGKATKAN KEBERANIAN MENGEMUKAKAN PENDAPAT PESERTA DIDIK - Memmy Dwi Jayanti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2014)
Abstract: Learning is a two way between teachers and students is very necessary in creating active learning atmosphere and fun, so that the teacher is no longer dominated learning but there is participation and involvement of the student. This research is done in class XI TKJ2 SMK PKP Jakarta Islamic School by the number of students by 22 people, precisely in the second semester begins in January to in May 2013. Purpose is to find effective learning strategies and efficient in teaching materials Indonesian with how to enable and foster courage students in an opinion on the learning process. After the application of the method of guided discussion learning conditions in the classroom look more lively and fun. Activeness and participation in exploring the material to make students more easily understand the material as well as influential in improving the value of their. Keywords: Guided Discussion Method, Opinion, Courage